How media shape the perception of temporary uses. A qualitative media analysis on vacancy and temporary uses in Vienna. - Matoga, Agnes (Taylor & Francis, 2019)
Temporary uses have a special position in traditional Viennese planning culture. Although practiced since the late 1990s, temporary projects have been gaining particular attention over the past couple of years. Additionally, the public discussion on vacancy in Vienna has gained momentum, and private and public agencies for temporary use have been recently formed in order to facilitate the communication between demand for and supply of affordable (vacant) space. Still, the number of temporary projects is rather conservative compared to other cities. Top-down regulatory requirements as well as personal preferences of property owners can be considered as reasons for increased or decreased temporary activities, and the media are believed to have potential influence on the practice of temporary projects. A media analysis of newspaper articles shows that: (i) temporary use is mentioned in connection with occupation movements in many cases - a clear differentiation between "illegal" and "informal" urban development is often times missing and misleading; (ii) the public discourse on vacancy and temporary use has clearly gained momentum and has been made visible to a large audience at a time when private intermediary actors have stepped in due to a lack of public management of vacant real estate; (iii) media analysis also shows that there is indeed a recognisable shift from top-down to more collaborative structures, however, established planning instruments and intensely bureaucratic processes still hinder informal bottom-up projects; and (iv) although there is a significant amount of Vienna-focused publications on these topics and propositions are being made on how to deal with vacancy, the city favours the development of governance tools to steer neighbourhood development rather than loosening legal frameworks and accepting in-formality, fuzziness and non-linearity as forms of urban development.
Keywords: Stadtentwicklung; Stadtplanung; Leerstand; Brache; Nutzungsänderung; Zwischennutzung; Erdgeschoss; Kreativwirtschaft; Empirische Untersuchung; Öffentliche Meinung; Presseauswertung